(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
Steel-concrete composite structure implies steel section encased in concrete for columns and the concrete slab or profiled deck slab is connected to the steel beam with the help of mechanical shear connectors so that they act as a single unit. Steel-concrete composite with Reinforced cement concrete options are considered for comparative study of G+15 storey office building which is situated in earthquake zone IV and for earthquake loading, the provisions of IS:1893(Part1)-2002 is considered by Equivalent Static Method of Analysis. For modeling of Composite & R.C.C. structures, STAAD. pro software is used. In this study, the seismic design and performance of composite steel-concrete frames are discussed in particular. Comparison of parameters like time period, displacement, moments and load carrying capacity is done with steel and Reinforced cement concrete structures. The results are compared and it is found that composite structure are more good in several aspect .